2014
DOI: 10.5194/acp-14-9105-2014
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of meteorological conditions and airflow connectivity during HCCT-2010

Abstract: This study presents a comprehensive assessment of the meteorological conditions and atmospheric flow during the Lagrangian-type "Hill Cap Cloud Thuringia 2010" experiment (HCCT-2010), which was performed in September and October 2010 at Mt. Schmucke in the Thuringian Forest, Germany and which used observations at three measurement sites (upwind, in-cloud, and downwind) to study physical and chemical aerosol-cloud interactions. A Lagrangian-type hill cap cloud experiment requires not only suitable cloud conditi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Entrainment of cleaner air from above might also reduce concentrations or, in the case of more polluted air mass from above, increases the concentration. However, during HCCT, the meteorological analysis as reported by Tilgner et al (2014) did not show strong entrainment from more polluted air masses especially during the selected events. In Fig.…”
Section: Aerosol Trace Metal Concentrationsmentioning
confidence: 71%
See 3 more Smart Citations
“…Entrainment of cleaner air from above might also reduce concentrations or, in the case of more polluted air mass from above, increases the concentration. However, during HCCT, the meteorological analysis as reported by Tilgner et al (2014) did not show strong entrainment from more polluted air masses especially during the selected events. In Fig.…”
Section: Aerosol Trace Metal Concentrationsmentioning
confidence: 71%
“…Cr, Cu, and Ni concentrations were found to be higher at GB. Although entrainment of more polluted air masses may lead to an increase in the concentration of trace metals in the downwind site, meteorological studies by Tilgner et al (2014) revealed a more stable stratification during this event with no large differences observed in the coefficient of divergence of the particles, suggesting that the possibility of entrainment of polluted air masses from above was rather low. These increased trace metals are often found from traffic emissions relating to car brake wear (Maenhaut et al, 2005) or from fuel combustion (Lee and Vonlehmd, 1973).…”
Section: Aerosol Trace Metal Size Distributionmentioning
confidence: 78%
See 2 more Smart Citations
“…In autumn 2010, the MARGA participated in the HCCT 2010 campaign in Goldlauter for two months (Tilgner et al 2014) and in an international CEN (European Committee for Standardization) field measurement campaign at the UBA site, Waldhof, from May until July 2014. Further data losses appeared due to maintenance and technical issues.…”
Section: Trajectory Calculation and Source Contribution Modellingmentioning
confidence: 99%